Effect of Inventory Management on Profitability: Empirical Evidence from Uniliver Nepal Limited - Karki, Chitra Bahadur (Journal of Management, 2020)
The study examines the effect of inventory management on the profitability of Uniliver Nepal Ltd. in Kathmandu. Secondary data have been collected from the annual financial statements of Uniliver Nepal Ltd. Kathmandu from fiscal year 2071/72 to 2075/76. A regression technique has been used considering statistical package Minitab 16 version to analyse the data. The study reveals the positive impact of efficient inventory management upon the profitability of Uniliver Nepal Ltd. in Kathmandu. Based on the findings the study recommends that Uniliver Nepal Ltd. should adopt effective and efficient inventory management practice, using appropriate modern technology for effective inventory management and employ capable and qualified staff who should be trained regularly on proper and efficient inventory management.